Economic Impact from the Existence of Universiti Tenaga Nasional (UNITEN) in Muadzam Shah Town, Pahang, Malaysia: An Input-Output Approach - Abdullah, Zulkifli; Ismail, Noraini; Bakar, Suzaida (International Journal of Engineering and Technology, 2018)
Muadzam Shah is a small town in Rompin District, Pahang, Malaysia, established in 1979 by the South-East Pahang Development Authority (DARA). It is a quiet and tranquil agricultural based economy area and is a brainchild of Malaysiaâ€™s second Prime Minister Tun Abdul Razak. The advent of University Tenaga Nasional in 2001 had changed the landscape of the local economy. Following the concept of â€œTown Universityâ€, UNITEN has successfully contributed to amplify the local economy into a greater level, from the oil-palm industry area to a multi-sectoral economy such as retailing sector, food industries, hospitality as well as healthcare industry. Besides, UNITEN also serves as a medium of community and intellectual development between the academia and the society. By adopting Leontief input-output approach, this paper is designed to determine the economic multiplier effect that students and faculty staffs have on the local economy and community in Muadzam Shah.